Quello che le terrecotte ci dicono ancora - Carboni, Romina; Cenci, Claudia; Chiarenza, Nicola (O T I V M, 2024)
The papers published in this volume were presented at the International Conference “What Can Terracottas Tell Us: Coroplastic Polysemy in the Ancient Mediterranean” (Cagliari - Cittadella dei Musei, 10–12th November 2022) organized under the scientific direction of Romina Carboni, Claudia Cenci and Nicola Chiarenza.